STUDI KOMPARASI TINGKAT KETERAMPILAN SOSIAL ANTARA SISWA SD DI KOTA DAN DESA - Febriana Lestari, Intan; Zainuddin, Almuntaqo (ATTA`DIB, 2024)
This study aims to compare the social skill development of elementary school pupils in urban and rural areas. The Social Skills Inventory (SSI) is a measuring tool used in this comparative study at SD Negeri Jetis 01 and SD Negeri Dukuh 03. Students in grade V are the study's subjects. Quantitative descriptive methods are employed in this comparative investigation. The study's findings indicate no discernible difference between elementary school pupils in cities and rural in terms of their social abilities.